Fear of Crime, Victimization, and Changes in Life Routines: A Structural Equation Model - Patricia Hernández-Medina; Daniel Goncalves Hernández; Diego Pinilla-Rodríguez; María Gonzalez Bautista (Kriminologie - Das Online-Journal)
The aim of this paper was to apply self-control/risky lifestyle theory on the risk of cyberstalking victimization in a younger age group by using a representative student sample from Germany. Results show that cyberstalking victimization is experienced by 18.2% of the representative sample of ninth-grade students. Girls were more often victimized than boys. Only a minority experience cyberstalking exclusively, whereas considerably more juveniles report having experienced both offline stalking and cyberstalking. The findings from the parallel multiple mediation models corroborate self-control/lifestyle theory and align with a growing body of literature indicating that low self-control has both direct and indirect effects on the risk of experiencing cyberstalking. For both genders, risk-seeking is significantly and positively associated with the risk of experiencing cyberstalking victimization, both directly and indirectly.